A Technique of Superficial Medial Collateral Ligament Reconstruction Using an Adjustable-Loop Suspensory Fixation Device - Shaneel Deo, B.H.B.(Hons), M.B.Ch.B., F.R.A.C.S.; Alan Getgood, M.Phil., M.D., F.R.C.S.(Tr&Orth), Dip.S.E.M. (Arthroscopy Techniques, 2015)
This report describes superficial medial collateral ligament reconstruction of the knee using a novel method of graft fixation with the ACL Tightrope RT (Arthrex, Naples, FL). After tibial fixation with either a standard interference screw or staple, femoral fixation of the semitendinosus tendon is performed with the adjustable-loop suspensory fixation device, which allows for both initial graft tensioning and re-tensioning after cyclical knee range of motion. This provides the ability for the graft to accommodate for resultant soft-tissue creep and stress relaxation, thereby allowing for optimal soft-tissue tension and reduction in laxity at the end of the procedure.